A Study on EduTainment: Enhancing Learning Activity in Science Learning - Andrie Kriesna Susilowaty; Nurhadji Nugraha; Yudi Hartono (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigates the effectiveness of Edutainment-based learning devices in enhancing learning activity in elementary school science learning. Methodology: A quantitative approach with a quasi-experimental posttest non-equivalent control group design was employed. The participants consisted of 14 fifth-grade students from an elementary school in Madiun City, Indonesia, divided into an experimental group (n = 7) and a control group (n = 7). The experimental group was taught using Edutainment-based learning devices, while the control group received conventional instructional tools. Data on students’ learning activity were collected using observation sheets based on a four-point Likert scale and analyzed using descriptive statistics, independent sample t-tests, and N-gain analysis at a significance level of 0.05. Main Findings: The findings reveal that students in the experimental group predominantly reached good (71.4%) and very good (28.6%) categories of learning activity, whereas the control group was dominated by not good (71.4%) and not very good (14.3%) categories. Inferential analysis confirmed a significant difference between the two groups (t = 4.167 > t_table = 2.145), indicating that Edutainment-based learning devices significantly outperform traditional approaches in promoting active learning. Moreover, an N-gain score of 0.6 suggests a moderate but meaningful improvement in students’ learning activity. Novelty/Originality of this study: The novelty of this study lies in its empirical validation of Edutainment-based learning devices specifically for IPAS at the elementary level, using learning activity as a core outcome rather than solely cognitive achievement.